2018
DOI: 10.1038/s12276-018-0057-6
|View full text |Cite
|
Sign up to set email alerts
|

Decipher reliable biomarkers of brain aging by integrating literature-based evidence with interactome data

Abstract: Aging is an inevitable progressive decline in every physiological function and serves as a primary risk factor for cognitive decline and Alzheimer’s disease. Thus, age-dependent impairments in cognitive function must be understood in association with general aging processes with an integrative approach in a systemic manner. An integrative aging gene network was constructed based on mutual molecular interactions using literature-curated interactome data and separated into functionally distinct modules. To inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…A network analysis of published transcriptomic data obtained from adult hippocampus samples has indicated that a module of genes that display age-dependent upregulation is enriched in myelination 39 . This study also confirmed an immune process-enriched module that correlated positively with age and a synaptic transmission-enriched module that correlated negatively with age 39 .
Fig.
…”
Section: Gene Coexpression Network Analysis Supports Decreased Synaptic Function and Increased Immune Function During Brain Agingmentioning
confidence: 99%
“…A network analysis of published transcriptomic data obtained from adult hippocampus samples has indicated that a module of genes that display age-dependent upregulation is enriched in myelination 39 . This study also confirmed an immune process-enriched module that correlated positively with age and a synaptic transmission-enriched module that correlated negatively with age 39 .
Fig.
…”
Section: Gene Coexpression Network Analysis Supports Decreased Synaptic Function and Increased Immune Function During Brain Agingmentioning
confidence: 99%
“…According to the CFG ranking, the top four genes (with 4 points each) were NPY, CXCL12, CCR5, and CNR2, and the genes in second place (with 2 points each) were PTGER3, MTNR1A, and GRM2 (Table 1). Several approaches have been used in previous research to identify potential target genes, such as ZFHX3, ERBB2, ERBB4, OCT3, MIF, CDK13, and GPI [27][28][29][30][31][32][33]. The most recent gene expression analysis conducted by Yan et al [34] identified the following hub genes: CDC42, VEGFA, BDNF, PDYN, CALB, TH, CACNA1A, OXT, CD44, and TAC1.…”
Section: Resultsmentioning
confidence: 99%
“…As a lipid metabolism-related molecule, the elevated myo-inositol in PB plasma may indicate the impairment in lipid metabolism in HIE, which was also present at urinary metabolomics [ 31 ]. Besides, metabolite set enrichment analysis also revealed several disturbed pathways closely related to brain dysfunction [ 40 , 41 ], including GABA synthesis, release, reuptake and degradation, fatty acid biosynthesis, and regulation of development of the central nervous system [ 42 ]. This further suggested that each metabolic pathway does not function independently but interacts with each other to perform its biological function, so the regulatory mechanism of this complex metabolic network needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%